2005
DOI: 10.1074/jbc.m506514200
|View full text |Cite
|
Sign up to set email alerts
|

MAPK-mediated Phosphorylation of GATA-1 Promotes Bcl-X Expression and Cell Survival

Abstract: In the interleukin 3-dependent hematopoietic cell line Ba/F3, inhibition of mitogen-activated protein kinase, a member of the MAPK/c-Jun N-terminal kinase/stressactivated protein kinase kinase family that plays an important role in cell growth and death control, rapidly leads to severe apoptosis. However, most of the antiapoptotic substrates of MAPK remain to be identified. Here we report that, upon interleukin-3 stimulation of Ba/F3 cells, the transcription factor GATA-1 is strongly phosphorylated at residue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 40 publications
6
45
0
Order By: Relevance
“…Interestingly, the anti-apoptotic function of GATA-1 has been found to be strongly dependent upon its phosphorylation at the serine 26 position (Yu et al, 2005). Here, we show that GATA-1 stimulates survivin gene transcription when phosphorylated on serine 26, indicating an upstream role for MAPK pathway in survivin overexpression in breast cancer cells.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Interestingly, the anti-apoptotic function of GATA-1 has been found to be strongly dependent upon its phosphorylation at the serine 26 position (Yu et al, 2005). Here, we show that GATA-1 stimulates survivin gene transcription when phosphorylated on serine 26, indicating an upstream role for MAPK pathway in survivin overexpression in breast cancer cells.…”
Section: Discussionmentioning
confidence: 57%
“…In erythroid cells exposed to erythropoietin, GATA-1 is the final effector of signalling pathways involving phosphatidylinositol-3-phosphate/protein kinase, B-Akt (Zhao et al, 2006), which phosphorylates the transcription factor on serine 310 (Kadri et al, 2005), and mitogen-activated protein kinase (MAPK) cascade, which phosphorylates GATA-1 on serine 26 and 178 (Towatari et al, 2004;Yu et al, 2005). Interestingly, the anti-apoptotic function of GATA-1 has been found to be strongly dependent upon its phosphorylation at the serine 26 position (Yu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have shown that the Bcl-xl gene promoter is regulated by NF-kB and its expression is regulated by the MAPK signaling pathway (Marinari et al, 2004;Yu et al, 2005) The Bcl-2 promoter contains a CRE that mediates its responsivity to the transcription factor (CREB) (Bonni et al, 1999;Riccio et al, 1999). Withdrawal of trophic support as well as an inhibition of CREB transcription triggers apoptosis in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that GATA-6 is a component of protein complexes bound to the GATA sites of the Nox1 promoter. Phosphorylation of GATA-1, -2, -3 and -4 is known to modulate their DNA-binding and protein-protein interactions resulting in cell-and gene-specific transcriptions (Morimoto et al, 2000;Patient and McGhee, 2002;Yu et al, 2005). Likewise, GATA-6 contains consensus ERK phosphorylation sites (PXS/TP: PYS 120 P, PYS 192 P and PMT 369 P) (Suzuki et al, 1996).…”
Section: Characterization Of the Functional Nox1 Promoter By Deletionmentioning
confidence: 99%